2008
DOI: 10.1677/joe-08-0270
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in phagocytic activity of splenic phagocytes in freshwater teleost Channa punctatus: melatonin and its signaling mechanism

Abstract: The aim of the present study was to understand the rhythmic changes in innate immune response in freshwater fish Channa punctatus. Furthermore, the putative role of melatonin as the zeitgeber was explored. The phagocytic activity of splenic phagocytes assessed at 6-h intervals showed higher phagocytic activity during light phase than dark phase. The increased phagocytic activity during light phase was diminished by melatonin administration at 09:00 h. Implication of melatonin in control of diurnal variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…One study reported evidence of diurnal rhythmicity in splenic phagocytic activity in a freshwater fish species ( Channa punctatus ) characterized by increased phagocytic activity during the light phase relative to the dark phase; the rhythmicity of the phagocytic activity was inhibited by exogenous melatonin administration [85]. Furthermore, the direct involvement of melatonin in the modulation of phagocytosis was demonstrated in in vitro experiments in which an irreversible tryptophan hydroxylase inhibitor (para-chlorophenylalanine, pCPA) known to diminish melatonin biosynthesis [86] was administered to fish.…”
Section: Effects Of Rhythms and Melatonin On The Fish Immune Systemmentioning
confidence: 99%
“…One study reported evidence of diurnal rhythmicity in splenic phagocytic activity in a freshwater fish species ( Channa punctatus ) characterized by increased phagocytic activity during the light phase relative to the dark phase; the rhythmicity of the phagocytic activity was inhibited by exogenous melatonin administration [85]. Furthermore, the direct involvement of melatonin in the modulation of phagocytosis was demonstrated in in vitro experiments in which an irreversible tryptophan hydroxylase inhibitor (para-chlorophenylalanine, pCPA) known to diminish melatonin biosynthesis [86] was administered to fish.…”
Section: Effects Of Rhythms and Melatonin On The Fish Immune Systemmentioning
confidence: 99%
“…Earlier Roy et al (2008) suggested that melatonin modulates the activity of Channa punctatus spleen phagocytes via a membrane receptor that is linked to the cAMP-PKA pathway, but no direct evidence for melatonin receptor expression was shown. In contrast, Confente et al (2010) did not find gene expression of MT1 receptors in blood cells of the Senegalese sole.…”
mentioning
confidence: 99%
“…In our earlier in vitro study in the wall lizard, dibutyryl cAMP was shown to inhibit the percentage phagocytosis and phagocytic index at higher concentrations (Roy and Rai, 2004). Also, an increased intracellular cAMP level in cortisoltreated (Roy and Rai, 2009) and melatonin-treated (Roy et al, 2008) splenic phagocytes is reported to be directly correlated with inhibition of phagocytosis in the freshwater fish Channa punctatus. In light of these studies, we speculated that dyn A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) would have inhibited the phagocytic activity of lizard splenic phagocytes by activating the  s subunit of the G-protein coupled to -opioid receptors and, consequently, by increasing the intracellular cAMP level.…”
Section: Discussionmentioning
confidence: 81%